2018 IEEE International Conference on Cloud Computing Technology and Science (CloudCom) 2018
DOI: 10.1109/cloudcom2018.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Using Quantile Regression for Reclaiming Unused Cloud Resources While Achieving SLA

Abstract: Although Cloud computing techniques have reduced the total cost of ownership thanks to virtualization, the average usage of resources (e.g., CPU, RAM, Network, I/O) remains low. To address such issue, one may sell unused resources. Such a solution requires the Cloud provider to determine the resources available and estimate their future use to provide availability guarantees. This paper proposes a technique that uses machine learning algorithms (Random Forest, Gradient Boosting Decision Tree, and Long Short Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Datrois et al [18] proposed a method that uses machine learning algorithms that predict the 24-h availability of resources at the host level. Their predicting method is based on the employment of quantile regression to ensure an elastic composition between the potential amount of resources to reclaim and to define unused resources.…”
Section: Machine Leaning Based Approachesmentioning
confidence: 99%
“…Datrois et al [18] proposed a method that uses machine learning algorithms that predict the 24-h availability of resources at the host level. Their predicting method is based on the employment of quantile regression to ensure an elastic composition between the potential amount of resources to reclaim and to define unused resources.…”
Section: Machine Leaning Based Approachesmentioning
confidence: 99%
“…To do so, the decision engine first verifies whether the fingerprint recognition model for the requested application is available. If not, it requests the Fingerprint Builder to generate one for this new application (2). Then, the Decision Engine chooses a suitable farmer that will be in charge of executing the customer application (3) [11].…”
Section: Methodsmentioning
confidence: 99%
“…A promising alternative for optimizing the cost of processing applications on Cloud infrastructures is to opportunistically exploit their allocated but momentarily unused computing resources [2]. Many platforms (e.g., BOINC [3], Condor [4]) enable the leveraging of these unused resources for a variety of purposes (e.g., scientific computing, big data) and business models (e.g., free, reward).…”
Section: Introductionmentioning
confidence: 99%
“…State-of-the-art studies have discussed [8] how to select the appropriate learning algorithm(s) to forecast time series with learning algorithms such as Autoregressive (AR), Integrated Moving Average (ARIMA) and other more complex algorithms such as Recurrent Neural Network (RNN), Support Vector Machine (SVM), Long short-term memory (LSTM), Gradient Boosted Decision Trees (GBDT), and Random Forest (RF). In a previous work [4] we have shown that quantile regression is a relevant approach to reclaim unused resources with SLA requirements. This work has shown that quantile regression may increase the amount of savings by up to 20% compared to traditional approaches.…”
Section: B Forecasting Buildermentioning
confidence: 99%
“…This over-provisioning increases the Total Cost of Ownership (TCO) for Cloud providers and results in a low average resource utilization. In a previous study [4], authors shown that the average CPU usage lies between 20% to 50% on several data centers.…”
Section: Introductionmentioning
confidence: 97%